Cover Picture: Highly Flexible Multifunctional Biopaper Comprising Chitosan Reinforced by Ultralong Hydroxyapatite Nanowires (Chem. Eur. J. 16/2017). Issue 16 (26th January 2017) - Sun, Tuan‐Wei; Zhu, Ying‐Jie; Chen, Feng
Abstract : The highly flexible multifunctional biopaper comprising ultralong hydroxyapatite nanowires and chitosan (UHANWs/CS) is shown in the cover picture. The reported biopaper has high flexibility, high biocompatibility, superior mechanical properties, and can be used for color printing. Moreover, the surface wettability, swelling ratio, and water‐vapor transmission rate of the biopaper are adjustable by changing the added amount of UHANWs. The as‐prepared biopaper is promising for various biomedical applications such as wound dressing, bone‐fracture fixation, and bone‐defect repair. More information can be found in the Full Paper by Y.‐J. Zhu, F. Chen, and T.‐W. Sun onpage 3850 ff.